Tanggap Tiga Varietas Padi Sawah terhadap Kombinasi Pemupukan dengan Sistem Pembenaman Jerami - Herdiyanti, Tri; ,, Sugiyanta; Aswidinnoor, Hajrial (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTDegradation of soil fertility due to inaccurate  application of fertilizer become one of the factors causing the stagnant rice productivity improvement in Indonesia. Straw incorporation, organic fertilizers and biofertilizers applications potentially reduces a rates of inorganic fertilizers and improves soil fertility. The aim of this study was to evaluate growth and yield of 3 lowland rice varieties (high yielding variety, new plant type, and local variety) in response to reduce NPK rates with straw incorporation, organic fertilizer, and biofertilizer in 7th planting season. The research was conducted at rice field in Karawang, West Java, from April-August 2013. The research was arranged in split plot randomized block design with 3 replications. The main plot was fertilizer application consisted of 10 treatments (combination of organic and inorganic fertilizers), while the sub plot was rice varieties (Ciherang, IPB 3S, and Mentik Wangi). The application of inorganic fertilizer, 400 kg NPK 30-6-8 ha-1, was control treatment. Plot size was 6.5 m x 10 m, with a double row spacing (25 cm x 15 cm x 50 cm). The result showed that growth of the three varieties was not significantly different so as the yield at 50% reduced NPK rate with incorporation of straw, organic fertilizer and biofertilizer. Adding of solid and liquid organic fertilizer, and biofertilizers on treatment of straw incorporation + 50% NPK rate was unnecessary due to insignificant yield increase.Keywords: Ciherang, fertilizer, IPB 3S, local variety, Mentik Wangi, new plant type